Why students feel competent in the classroom: A qualitative content analysis of students’ views - Reymond, Nadia Catherine; Nahrgang, Ruth Gerlinde; Großmann, Nadine; Wilde, Matthias; Fries, Stefan (Frontiers in Psychology, 2022)
This qualitative study aimed to identify and to systematize factors that contribute to students’ competence satisfaction in class from students’ perspectives. Based on self-determination theory as our primary theoretical background, we conducted episodic interviews with 25 high school students. A combined deductive-inductive qualitative content analysis approach was applied. As our key finding, we revealed different teaching factors within and beyond self-determination theory (i.e., structure, autonomy support, relatedness support, mastery goal structure, perceived error climate, teaching quality, teachers’ reference norm orientations) as well as additional factors (e.g., students’ motivation and engagement, peer climate and reciprocal peer support) that contributed to students’ competence satisfaction in class from the students’ points of view. This study contributes to existing research on why students’ competence satisfaction arises in class by complementing it with an integrative, explorative, and student-oriented perspective.